ANALISIS TATA RUANG KANTOR DAN PRODUKTIVITAS KERJA TENAGA ADMINISTRASI DI SMAN 4 WIRA BANGSA MEULABOH - Nofriandi; Hardianty, Sri; Zulfahmi, Junias (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2025)
This study aims to analyze the office layout and work productivity of school administrative staff at SMAN 4 Wira Bangsa Meulaboh. A qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings reveal that a well-organized office layout—with a closed-plan design, flexible furniture arrangement, and attention to lighting, air circulation, and cleanliness—creates a comfortable and conducive work environment. This directly contributes to increased work productivity among administrative staff, as indicated by high work quantity, good work quality, and timely task completion. However, certain issues remain, such as dim lighting in some corners of the office and suboptimal air conditioning due to the absence of glass doors, indicating the need for improvements in physical facilities. Therefore, ergonomic office space management and support for the professional development of administrative staff are key to fostering a productive work environment in schools.